Modeling changes in nutrient retention ecosystem service using the InVEST-NDR model: A case study in the Gumara River of Lake Tana Basin, Ethiopia - Abebe, Wubneh B.; Dersseh, Minychl G.; Goshu, Goraw; Worku, Wuletawu Abera; Abraham, Edo; Mekonnen, Muluneh A.; Fohrer, Nicola; Tilahun, Seifu A.; McClain, Michael E.; Payne, William A.; Blaszczak, Joanna R. (Elsevier, 2025)
Aquatic ecosystems provide valuable ecosystem services (e.g., habitat for fisheries) to surrounding communities but environmental degradation can diminish the quality of these ecosystem services. The Lake Tana basin, including the Gumara River and its associated wetlands in Ethiopia, has experienced rapid environmental change in the last several decades. Changes in the export of nutrients from the uplands might contribute to the rapid degradation of aquatic ecosystem services due to the expansion of water hyacinths and declines in fish biodiversity and yields. We estimate how human modification and climate change have impacted watershed nutrient retention from 1986 to 2020. Here we (1) examine trends in surface water chemistry, watershed land use/land cover change, and flow alterations; (2) estimate the watershed nutrient delivery ratio (NDR), a metric of watershed nutrient retention, through time; and (3) examine how fishery yields and water hyacinth infestation in Lake Tana at the outlet of the Gumara River change during a period of rapid increase in nutrient export from the Gumara River. Estimates of the surface load and export of both phosphorus (P) and nitrogen (N) from the Gumara River watershed were approximately stable between 1986 and 2009, but from 2014 to 2020 exports increased by 69 % for P and 80 % for N. Potential factors driving this rapid increase include an expansion in irrigation for agriculture, land conversion to eucalyptus plantations, decreases in dry season flow, and an increase in mean annual precipitation since 2009. In addition, the increase in nutrient export from the Gumara River watershed coincides with a near extirpation of fish in the Gumara River and a ten-fold expansion of water hyacinth downstream in Lake Tana. Human activity and hydrological alteration in the Gumara River watershed have resulted in water quality changes, declines in fish populations, and the expansion of invasive species. Long-term monitoring and watershed modeling can help inform the management of regionally important aquatic ecosystems such as the Gumara River and Lake Tana.